Decoding complexity: tackling the challenge of how many transcription factors regulate a plant gene - Gray, John; Grotewold, Erich (Transcription, 2025)
The regulation of transcription is a major control point in the flow of information from the genome to the phenome. Central to this regulation are transcription factors (TFs), which bind specific DNA motifs in gene regulatory regions. In both metazoans and plants, 5-7% of all genes encode TFs. Although individual TFs can recognize and regulate thousands of target genes, an important question remains: how many TFs are required to precisely control the expression of a single gene? In this review, we compare the regulation of gene expression in plants and metazoans, outline key methodologies for identifying genes recognized or regulated by TFs, and explore what is currently known about the number of TFs needed to define the expression of any given plant gene. As the volume of high-throughput sequencing data continues to grow exponentially, it becomes increasingly clear that transcriptional regulatory networks exhibit remarkable complexity, characterized by many targets influenced by each TF; and that many TFs, often several dozens, contribute to the regulation of individual genes.